A Simple Approach to Teach Newton’s Third Law - Mansyur, J.; Kaharu, S. N.; Holdsworth, J. (Jurnal Pendidikan IPA Indonesia, 2020)
The results of previous researches indicated that there were problems with the mental model and students’ conceptual understanding of the action-reaction law (Newton’s third law, NTL). This research aimed to reveal the effect of a simple approach in teaching NTL. The research was conducted in the first-year of pre-service physics teachers at the Physics Education Department of Tadulako University. Research designs for three consecutive years were (1) one-group, pre-test, and post-test design, (2) a static group comparison (pre-test for the experimental group), and (3) a quasi-experimental. The approach used was an interactive demonstration that consisted of five phases, i.e: eliciting an intuitive argument, demonstrating a continuous force: pulling, demonstrating a continuous force: pushing, demonstrating impulsive force: collisions, and refining the concept with Elby’s pair. Data were collected using a multiple-choice test developed in previous research. The results of the data analyses showed that the approach could improve students’ understanding of the action-reaction law, supporting conceptual change by exhibiting N-gain in the moderate and high categories. The instructional design can be considered for implementation in learning in high schools, lecture on pre-service physics teachers and basic physics lecture, in general..